THE PROBLEM OF INSTRUCTIONAL TEACHER TRAINING OF HIGHER EDUCATION INSTITUTION - Кокарєва, А. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article deals with the place and role of teachers' methodical training, which is one of the most important conditions of effectiveness increasing in their professional activity. The article highlightes aspects of present methodical training of higher education institutions teachers, the necessity of such training is shown